Forecasting paddy production at Muda Agricultural Development Authority (MADA) / Norziela Binti Rosli - Rosli, Norziela (2011)
This study is concerned to the application of forecasting techniques for some selected paddy production by MUDA agricultural development authority (MADA) which covers the period of 1990 until 2010.The objectives of this study are to identify the pattern of paddy production, to determine the best forecasting model and to predict the forecast values for year 2011 to 2015. Three different model types of forecasting are chosen for comparisons which are the naïve model, methods of average and exponential smoothing techniques, and the Box-Jenkins Methodology. All the best models of forecasting for paddy production are identified and selected based on the minimum of Mean Square Error (MSE) and Root Mean Square Error (RMSE) value. According to the results, the Box-Jenkins Methodology with ARIMA modeling fit all the price series well and they are capable of predicting the future values. As a conclusion the best forecasting model for paddy production by MADA is ARIMA (1,2,1)